The Use of Manipulative Media to Improve Elementary School Students’ Understanding of Fraction Concepts - Majid, Abdul; Syarifuddin, Syarifuddin (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although students’ understanding of fraction concepts in elementary mathematics has received increasing scholarly attention, research specifically examining the use of manipulative media to improve conceptual understanding in rural primary school contexts remains limited. This study aims to evaluate the effectiveness of manipulative media in enhancing students’ understanding of fraction concepts at SDN 38 Bonto Perak, Pangkep Regency. A Classroom Action Research (CAR) design was employed, involving 20 students selected through purposive sampling. Data were collected through achievement tests, observation sheets, and documentation, and analyzed using descriptive quantitative techniques. The findings indicate that the use of manipulative media improved students’ conceptual understanding of fractions, as reflected in an increase in the average score from 62 in Cycle I to 82 in Cycle II and an improvement in learning mastery from 45% to 85%. These results suggest that manipulative media can facilitate hands-on and meaningful learning by helping students construct a clearer understanding of abstract fraction concepts. This study contributes to the literature on constructivist learning and elementary mathematics education by providing empirical evidence on the role of manipulative media in strengthening conceptual understanding. Practically, the findings imply that teachers should integrate manipulative media consistently into classroom instruction to enhance student engagement, conceptual comprehension, and mathematics learning outcomes.